A new false‐root identification method based on two‐terminal fault location algorithm for double‐circuit transmission lines. Issue 6 (9th July 2017) - Wang, Shoupeng; Zhao, Dongmei
Abstract : A fault location algorithm without synchronization for double‐circuit transmission lines does not require sampling synchronization, reduces the cost, and has a higher engineering value, but the algorithm still needs to be improved in the false‐root identification. This paper conducts further studies on this issue. First, the false‐root problem of the fault location algorithm without synchronization is analyzed, and then a new false‐root identification method is proposed, which is based on the difference of the existence of the false root in the calculation of the voltage amplitude along the line with different electrical moduli. It can solve the problem of the traditional method, which cannot distinguish between voltage amplitudes when they are close. Second, considering the shortcoming of the existing phase‐mode transformation matrix, a new phase‐mode transformation matrix applied to double‐circuit lines is deduced, which is based on the six‐sequence component method; it can be combined with the new false‐root identification method, thereby realizing false‐root identification under various types of faults. Finally, fault location is realized by using the moduli in the mold domain. The principle does not need to synchronize data in two terminals and is not affected by the fault types, fault resistances, and other factors. As is shown in a large number of Alternative Transients Program version of Electro‐Magnetic Transients Program (ATP‐EMTP) simulation results, the fault location has a higher accuracy © 2017 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.